Performance Analysis of Data Traffic Offload Scheme on Long Term Evolution and IEEE 802.11AH - Made Adi Paramartha Putra; Doan Perdana; Ridha Muldina Negara (Universitas Ahmad Dahlan, 2017)
One of new mobile technology is being developed by 3GPP is Long-Term Evolution (LTE). LTE usually used by user because provide high data rate. Many traffic sending over LTE, makes several users didn’t get good Quality of Service (QoS). Traffic diversion is needed to increasing QoS value. It can be done with offloading data method from LTE to Wi-Fi network. This paper using 802.11ah standard to evaluate Wi-Fi network. IEEE 802.11ah have 1000 meters coverage area and efficiency energy mechanism, which is proposed for M2M in 5G techonology. Some research has proven that traffic diversion with offloading can increasing network performance. The contribution of this paper is to evaluate the impact of traffic offload between LTE and IEEE 802.11ah standard. This paper propose two scenarios using increment number of user and increment mobility speed of user to evaluate throughput and delay value before and after the offload process. The simulation will simulate using Network Simulator-3. We can conclude that network performance after offloading is better for every scenario. For increment number of user scenario, throughput value increasing 29.08%, and delay decreasing 8.12%. Scenario with increment mobility speed of user obtain throughput value increasing 37,57%, and delay value decreasing 27.228%.